Microbial Methane Generation and Implications for Stability of Shallow Sediments on the Upper Slope, U.S. Atlantic Margin - Carty, Olin R.; Daigle, Hugh (Frontiers in Earth Science, 2022)
Dissociation of methane hydrates in shallow marine sediments due to increasing global temperatures can lead to the venting of methane gas or seafloor destabilization. Along the U.S. Atlantic margin there is a well-documented history of slope failure and numerous gas seeps have been recorded. However, it is not fully understood whether the observed gas seepages can lead to slope failure as seafloor data is often sparse. We used machine learning algorithms to predict total organic carbon (TOC) and porosity at the seafloor on the U.S. Atlantic margin. Within this region, an area of high TOC predictions (1.5 – 2.2% dry weight) occurred along the continental slope from (35.4°N, 75.0°W) to (39.0°N, 72.0°W), aligning with documented gas seeps in the region. Elsewhere, predicted values of TOC were near or below 1% dry weight. In the area of high TOC, we modeled hydrate and gas formation over a 120,000 year glacial cycle. Along the feather edge, average hydrate saturations at the base of the hydrate stability zone (BHZ) were between 0.2% and 0.7% with some models predicting hydrate saturation above 3% and average peak gas saturations ranged from 4% to 6.5%. At these locations we modeled the pore pressure response of sediments at the BHZ to hydrate dissociation due to an increase in temperature. We focused on purely drained and undrained loading environments and used a non-linear Hoek-Brown failure envelope to assess whether failure criteria were met. In a drained loading environment, where excess pore pressure is instantly dissipated, we found that the change in effective stress due to hydrate dissociation is small and no failure is expected to occur. In an undrained loading environment, where excess pore pressure does not dissipate, the change in effective stress due to hydrate dissociation is larger and shear failure is expected to occur even at low hydrate saturations (0.2% – 1%) forming final gas saturations below 0.1%. Therefore, we conclude that the dissociation of hydrates along the feather edge can lead to the conditions necessary for sediment failure.